Active-passive voice shift in English translations of A.Samad Said’s Salina / Hamizah Hasbullah - Hamizah , Hasbullah (2019)
This study is aimed to investigate occurrences of active-passive voice shifts in three English translations of Salina (A.Samad Said) by Harry Aveling (1975), Hawa Abdullah (1991) and Lalita Sinha (2013); to compare active and passive voice use between TTs and to identify the factors which have influenced the translators’ active-passive voice shifts in their translations. The analysis was done on three translations of Salina from Malay into English and each text was analyzed to mark every clause with active intransitive and active transitive verbs; and passive verbs. They were categorized and counted. Other types of sentences and phrases were also counted and labelled under category ‘others’. Then, the occurrences of active-passive voice shifts were analysed and counted throughout the texts. The results show that there are four types of voice shifts found: active intransitive to passive shift, active transitive to passive shift, passive to active intransitive shift and passive to active transitive shift. Active intransitive to passive shift has more occurrences than active transitive to passive shift. However, there is only a slight difference in number where active intransitive outnumbers active transitive with 1 occurrence. The findings also reveal that the active-passive voice shift occurs more in a single translation than in multiple translations. Passive to active transitive shift has higher number of occurrence than passive to active intransitive shift. The results also demonstrate that the passive to active voice shift occurs mostly in multiple translations. To compare between the four types of voice shift, passive to active transitive shift showed the highest number of occurrence. This concluded that the use of active voice is more preferable in the English translations. Three main factors influenced the voice shift in the studied data: translator’s choice, the syntactical difference between Malay underlying structure and English structure and the difference between Malay morphological voice markers and English voice markers. Most of the voice changes were due to the translator’s choice. This factor is identified when there is no language peculiarity in the ST sentence and the change was not obligatory. The changes mostly were made to serve stylistic purposes. Next, the shifts occurred due to the difference between Malay structure and English structures. It is found that if the SL structure is retained, it would sound strange in the TL. The voice shifts were made considering TL acceptability. Finally, the changes also occurred when it involved ambiguous Malay morphological voice markers. Prefix ‘ter-’, for example, can be active and passive. In the data samples, it was shown that only ‘ter-’ active was found and they were changed into the passive voice in the English translations.